Dinamika Pencemaran Tanah oleh Logam Berat dan Potensi Bioremediasi sebagai Strategi Pemulihan Lingkungan di Pulau Lombok: Tinjauan Literatur - Dewi Saraswati; Lolita Endang Susilowati (Jurnal Zona, 2026)
Soil plays an essential role in maintaining ecosystem balance, supporting agricultural productivity, and facilitating various biogeochemical processes. However, increasing human activities such as small-scale mining, intensive agriculture, waste disposal, and land use changes have increased the risk of heavy metal contamination in soils. Heavy metals including mercury (Hg), lead (Pb), cadmium (Cd), and arsenic (As) are toxic, persistent, and capable of accumulating in food chains, posing risks to environmental sustainability and human health. This study aims to examine the forms of soil contamination caused by heavy metals in Lombok Island, identify effective bioremediation approaches for reducing heavy metal concentrations in soil, and analyze the most promising methods for improving the quality of contaminated soils. The research employed a qualitative descriptive approach using a literature review method. Scientific articles were collected from academic databases such as Google Scholar, ScienceDirect, and SpringerLink, focusing on publications from the last decade related to soil contamination and bioremediation. The selected literature was analyzed and synthesized by categorizing findings based on sources of contamination, ecological impacts, and bioremediation strategies. The results indicate that soil contamination in Lombok is primarily influenced by artisanal gold mining activities, waste management practices, and uncontrolled land use changes. Various studies highlight that biological remediation approaches, particularly those involving microorganisms, have strong potential to reduce heavy metal toxicity while improving soil fertility and ecological functions. Therefore, bioremediation represents a sustainable and environmentally friendly strategy for restoring contaminated soils and supporting long-term environmental management